2018
DOI: 10.1111/cea.13258
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrocurcumin, a major metabolite of curcumin, ameliorates allergic airway inflammation by attenuating Th2 response and suppressing the IL‐4Rα‐Jak1‐STAT6 and Jagged1/Jagged2 ‐Notch1/Notch2 pathways in asthmatic mice

Abstract: The above results demonstrated for the first time that THC was superior to Cur in modulating allergic asthmatic phenotypes, especially attenuating the Th2 response. THC might be a potentially effective agent for asthma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 37 publications
(57 reference statements)
0
36
0
7
Order By: Relevance
“…Our previous study demonstrated that the immune-modulating properties of THC against asthma were at least partly targeted to the inhibitory effects of the Th2 response by suppressing the IL-4Rα-Jak1-STAT6 and Jagged1/Jagged2-Notch1/Notch2 pathways [10]. Similarly, DEX treatment significantly decreased the number of eosinophils, Th2 cells, and Th2 cytokines [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study demonstrated that the immune-modulating properties of THC against asthma were at least partly targeted to the inhibitory effects of the Th2 response by suppressing the IL-4Rα-Jak1-STAT6 and Jagged1/Jagged2-Notch1/Notch2 pathways [10]. Similarly, DEX treatment significantly decreased the number of eosinophils, Th2 cells, and Th2 cytokines [23].…”
Section: Discussionmentioning
confidence: 99%
“…Four-week-old BALB/c mice (female) were purchased from Sun Yat-sen University Animal Center (Guangzhou, China) and were housed in a specific pathogen-free facility. The murine model of allergic asthma was established as previously reported [9, 10]. First step: mice were sensitized via i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Curcumin is a phenolic pigment that is extracted from the rhizome of Curcuma longa, and it is a main active ingredient with strong antiinflammatory and antioxidant effects. [2][3] The Notch signaling pathway exists widely in vertebrates and non-vertebrates, and it is highly conserved in evolution. Both humans and rats have four Notch receptors.…”
Section: Introductionmentioning
confidence: 99%
“…IL-4 production in mast cells has been studied in relation to IgE-mediated activation [8,9]. IL-4 is a multifunctional cytokine that plays an important role in inducing allergic Th2-type immune responses [10]. IL-4 activates signal transducers and activators of transcription 6 (STAT6) and induces the expression of IL-4-inducible genes, including class II major histocompatibility molecules, low-a nity IgE receptor, and IL-13 [9,11] [7].…”
mentioning
confidence: 99%